Insights into SARS-CoV-2 genome, structure, evolution, pathogenesis and therapies: Structural genomics approach - Naqvi, Ahmad Abu Turab; Fatima, Kisa; Mohammad, Taj; Fatima, Urooj; Singh, Indrakant K.; Singh, Archana; Atif, Shaikh Muhammad; Hariprasad, Gururao; Hasan, Gulam Mustafa; Hassan, Md. Imtaiyaz (Biochimica et biophysica acta. Molecular basis of disease, 2020)
The sudden emergence of severe respiratory disease, caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has recently become a public health emergency. Genome sequence analysis of SARS-CoV-2 revealed its close resemblance to the earlier reported SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV). However, initial testing of the drugs used against SARS-CoV and MERS-CoV has been ineffective in controlling SARS-CoV-2. The present study highlights the genomic, proteomic, pathogenesis, and therapeutic strategies in SARS-CoV-2 infection. We have carried out sequence analysis of potential drug target proteins in SARS-CoV-2 and, compared them with SARS-CoV and MERS viruses. Analysis of mutations in the coding and non-coding regions, genetic diversity, and pathogenicity of SARS-CoV-2 has also been done. A detailed structural analysis of drug target proteins has been performed to gain insights into the mechanism of pathogenesis, structure-function relationships, and the development of structure-guided therapeutic approaches. The cytokine profiling and inflammatory signalling are different in the case of SARS-CoV-2 infection. We also highlighted possible therapies and their mechanism of action followed by clinical manifestation. Our analysis suggests a minimal variation in the genome sequence of SARS-CoV-2, may be responsible for a drastic change in the structures of target proteins, which makes available drugs ineffective. Schematic representation of novel corona virus showing target proteins and its mechanism of host entry. [Display omitted] •The recent exposure to SARS-CoV-2 has affected entire world, resulted >0.4 million deaths.•Potential drug targets of SARS-CoV-2 are highly conserved.•A slight structural difference makes available drugs ineffective against SARS-CoV-2.•Cytokine storm during SARS-CoV-2 infection may be targeted to handle COVID-19 patients.•Many FDA approved drugs are showing positive effects in clinical trials but further validation in large subject groups is required.